Analysis of employee costs in the distributive trade of Bosnia and Herzegovina - Ribić, Fatima (Ekonomija - teorija i praksa, 2023)
Distributive trade includes all forms of trading activities. It begins with the procurement of goods from the manufacturer, and ends with the sale of goods to the final consumer. In Bosnia and Herzegovina, it represents one of the most important economic sectors. Thispaper investigates changes in personnel costs within the distribution trade sector in Bosnia and Herzegovina. Initially, it introduces fundamental concepts related to distributive tradeand personnel costs. After that, an analysis of personnel costs in the distribution trade sector in Bosnia and Herzegovina is conducted. This includes an examination of changes in personnel costs based on the size of business entities and an analysis of personnel costs in subsectors of distribution trade. Research findings reveal a consistent increase in personnel costs within the distribution trade sector in Bosnia and Herzegovina from 2016 to 2021. They also highlight a slower growth of personnel costs per employed person in small businesses compared to the overall sector. Concerning the sub-sectors of distribution trade in Bosnia and Herzegovina, the research indicates that wholesale trade demonstrates significantly higher personnel costs per employed person compared to the other two sub-sectors and the overall distribution trade. Additionally, the analysis involves a comparison of personnel costs in distribution trade in Bosnia and Herzegovina with other countries in the region. The findings suggest that personnel costs per employed person in the distribution trade sector in Bosnia and Herzegovina exhibit the lowest growth among the analyzed countries in the region.